Skill-based differences in visual search behaviours and verbal reports in a representative film-based task in volleyball - Afonso, J.; Mesquita, I. (International Journal of Performance Analysis in Sport, 2013)
A desire to increase understanding of the mechanisms underpinning expert performance has motivated a large body of research. We examined the processes supporting skilled performance in a complex film-based volleyball task using a representative simulated environment. Participants were presented a complex, game-like volleyball task. We combined eye movement recording with immediate retrospective verbal reports of thinking in fifteen elite female volleyball players, ranked into skilled and less skilled groups. Skilled players employed longer fixations than their less skilled counterparts, and spent a greater amount of time fixating the receiver and functional spaces between two or more players. Skilled participants generated significantly more condition concepts, and presented a superior level of sophistication in their verbal reports. Data suggests that it is relevant to use tasks that simulate real-life environments. The definition of functional spaces, aiming for locations that stimulate retrieving information from more than one cue at a time, affords researchers to use eye-tracking devices to analyze peripheral vision. Based on collection of verbal reports researchers could assess if those functional spaces were relevant for the subjects. Researchers need to be thoughtful when designing representative tasks in order to accurately simulate competitive contexts.